Kreowanie doświadczeń liminalnych w szkole z wykorzystaniem metody dramy edukacyjnej - Jaskulska, Sylwia (Studia Edukacyjne, 2020)
The aim of the paper is to consider the possibility of creating liminal experiences at school with the method of educational drama and the pedagogical potential of such activities. Treated as the medium phase of rite, I define liminality in line with Arnold van Genepp and Victor Turner. By claiming that for many reasons school is a liminal space and showing that the fact that this function is neglected at the cost of the transmission function is a problem, I present drama as a possible antidote.